Analyse du traitement médiatique du silure glane (Silurus glanis), une espèce au centre de controverses - Jean-Marie Bodt; Frédéric Santoul; Muriel Lefebvre (VertigO)
The introduction of the European catfish (Silurus glanis) in French rivers is frequently covered by the media. In these articles, one of the main issues is the undesirable aspect of this species : it would be invasive and would disrupt the balance of aquatic ecosystems. However, the first scientific research on the issue (Valadou., 2007 ; Proteau et al., 2008) tends to dispute these statements. Since then, the catfish finds itself at the center of controversies. To explore the content of these debates, we analyzed the media coverage of catfish in national and local newspapers from 2003 to 2015. By applying lexical data mining, we identified different lexical unities, revealing debates surrounding catfish. Then, through a qualitative exploration of the texts, we listed the different ways to designate catfish and its impact on aquatic environments. We show that negative representations continued to be covered by media stories. Indeed, although we can observe an evolution of journalistic discourse, debate continues over the entire period. Despite the empirical findings of science, some stakeholders continue to accuse the amount of catfish of ecological disorders. This focus on invasive species shows how judgement is mainly based on the alien character of the species.